PENATAAN PENGUASAAN TANAH Strategi Mereduksi Bahaya Banjir - Riyadi, Rakhmat (MAGISTRA, 2011)
The danger of flood threatens all Indonesian regions, especially in a rainy season. The handling of flood,so far, has not yet been very successful. Therefore, a certain strategy is needed to overcome the danger throughoutthe regions.The land use strategy was assumed to be one of the strategies which was able to applied to reduce theabove danger. The Indonesian government, both the central and regional governments, had to be able to takethe role in facilitating and urging the application of the above strategy.Key words : Land tenure, land use, flood